Eliminating hunger in a world serious about climate mitigation - Jennifer A. Burney (Proceedings of the National Academy of Sciences, 2025)
What will it take to eliminate hunger in a world that is increasingly serious about climate change mitigation? For the past two decades, climate activism and mitigation efforts have largely focused on energy, industry, and transportation as the main contributors to anthropogenic warming. Although there is a long way to go to eliminate emissions from these sources, increasing international ambition means that attention is now turning to other hard-to-decarbonize sectors. Net zero food systems in particular pose unique challenges for humanity, given the moral dimensions of food security and the strong potential for vicious cycles: Globally hunger is back on the rise, the changing climate is already making food production for a growing population more difficult, and food shocks could lead to more land use change emissions that accelerate warming and feed back to negatively impact agricultural productivity and hunger. The dynamics of food production and consumption differ from other sectors and reveal several dimensions in which it will be critical to get policy right. Recent science suggests that two coordinated efforts will be needed to meet this challenge—a revamped focus on smallholder adaptation and productivity, and new “safety valve” institutions that sit at the intersection of food production and climate mitigation efforts and can operate at the relevant spatial and temporal scales to avoid negative tradeoffs in the quest to eliminate hunger and stabilize earth’s climate.